The effects of plyometric jump training on jumping and swimming performances in prepubertal male swimmers - Sammoud, S.; Negra, Y.; Chaabene, H.; Bouguezzi, R.; Moran, J.; Granacher, U. (Journal of Sports Science & Medicine, 2019)
Swimming performance can be improved not only by in-water sport-specific training but also by means of dry land-training (e.g., plyometric jump training [PJT]). This study examined the effects of an 8-week PJT on proxies of muscle power and swimming performance in prepubertal male swimmers. Participants were randomly allocated to a PJT group (PJT; n = 14; age: 10.3 ± 0.4 years, maturity-offset = -3±0.3) or a control group (CG; n = 12; age: 10.5 ± 0.4 years, maturity-offset = -2.8 ± 0.3). Swimmers in PJT and CG performed 6 training sessions per week. Each training session lasted between 80 and 90 minutes. Over the 8 weeks in-season training period, PJT performed two PJT sessions per week, each lasting between 25 to 30 minutes (~1 hour per week) in replacement of sport-specific swimming drills. During that time, CG followed their regular sport-specific swimming training (e.g., coordination, breathing, improving swimming strokes). Overall training volume was similar between groups. Pre- and post-training, tests were conducted to assess proxies of muscle power (countermovement-jump [CMJ]), standing-long-jump [SLJ]) and sport-specific swimming performances (15-, 25-, and 50-m front-crawl, 25-m kick without push [25-m kick WP], and 25-m front-crawl WP). No training or test-related injuries were detected over the course of the study. Between-group analyses derived from magnitude-based inferences showed trivial-to-large effects in favour of PJT for all tests (ES = 0.28 to 1.43). Within-group analyses for the PJT showed small performance improvements for CMJ (effect-size [ES] = 0.53), 25-m kick WP (ES = 0.25), and 50-m front crawl (ES = 0.56) tests. Moderate performance improvements were observed for the SLJ, 25-m front-crawl WP, 15-m and 25-m front-crawl tests (ES = 0.95, 0.60, 0.99, and 0.85, respectively). For CG, the within-group results showed trivial performance declines for the CMJ (ES=-0.13) and the 50-m front-crawl test (ES = -0.04). In addition, trivial-to-small performance improvements were observed for the SLJ (ES = 0.09), 25-m kick WP (ES = 0.02), 25-m front-crawl WP (ES = 0.19), 25-m front-crawl (ES = 0.2), (SLJ [ES = 0.09, and 15-m front crawl (ES = 0.36). Short-term in-season PJT, integrated into the regular swimming training, was more effective than regular swimming training alone in improving jump and sport-specific swimming performances in prepubertal male swimmers. Key Points